THE STATE OF THE RESEARCH OF THE PROBLEM OF DEVELOPMENT OF INTELLECT AND CAPABILITY IN CHILDREN OF PRE-SCHOOL AGE IN THE WORK OF DOMESTIC AND FOREIGN SCIENTISTS - Bida, Olena; Kuchai, Olexander; Chychuk, Antonina (Mountain School of Ukrainian Carpaty, 2019)
The article deals with the state of research of the problem of studying the development of intelligence and giftedness in preschool children in the works of domestic and foreign scientists. It was found out that the problem of education and training of a gifted child of preschool age was the subject of research in the work of teachers and psychologists of different historical periods, but despite a considerable theoretical and practical heritage, some aspects of this multifaceted question require a more thorough understanding, first of all, given the urgency of the development of a gifted child of preschool age at the present time. The assimilation of the pedagogical heritage of famous domestic and foreign scientists is an important prerequisite for the formation of students 'and teachers' pedagogical skills, the awareness of the need to creatively use historical and pedagogical ideas in modern education for working with gifted children. The development of scientific research makes it possible to more successfully solve the problem of the development of gifted and talented children not through spontaneous selection but on the basis of modern knowledge about the nature of giftedness, the development of psychological means of stimulation and assistance to gifted and talented children. Purpose and tasks. To find out the state of research of the problem of studying the development of intelligence and giftedness in children of preschool age in the works of domestic and foreign scientists. In the article methods of research are used: theoretical (analysis of philosophical, pedagogical, psychological literature), for substantiation of initial research positions; the interpretive-analytical method on the basis of which Ukrainian and foreign sources were studied using synthesis, analysis, systematization and generalization.